Regulation of COP1 Function by Brassinosteroid Signaling - Nieto, Cristina; Luengo, Luis Miguel; Prat, Salomé (Frontiers in Plant Science, 2020)
Small increases in temperature result in enhanced elongation of the hypocotyl and petioles and hyponastic growth, in an adaptive response directed to the cooling of the leaves and to protect the shoot meristem from the warm soil. This response, collectively termed as thermomorphogenesis, relies on the faster reversion of phyB Pfr at warmer temperatures, which leads to enhanced activity of the basic-helix-loop-helix PHYTOCHROME INTERACTING FACTOR 4 (PIF4). PIF4 acts as a molecular hub integrating light and temperature cues with endogenous hormonal signaling, and drives thermoresponsive growth by directly activating auxin synthesis and signaling genes. Growth promotion by PIF4 depends on brassinosteroid (BR) signaling, as indicated by the impaired thermoresponse of BR-defective mutants and the partial restoration of pifq thermoresponsive defects by brassinolide (BL) application. Also, phyB limits thermomorphogenic elongation through negative regulation of the E3 ubiquitin ligase COP1 that triggers nuclear degradation of multiple photomorphogenesis-promoting factors acting antagonistically to PIF4. COP1 is indeed observed to accumulate in the nucleus in darkness, or in response to warm temperatures, with constitutive photomorphogenic cop1 mutants failing to respond to temperature. Here we explored the role of BR-signaling on COP1 function, by growing cop1 seedlings on BL or the inhibitor brassinazole (BRZ), under different light and temperature regimes. We show that weak cop1 alleles exhibit a hyposensitive response to BL. Furthermore, while cop1-6 mutants display as described a wild-type response to temperature in continuous darkness, this response is abolished by BRZ. Application of this inhibitor likewise suppressed temperature-induced COP1 nuclear accumulation in N. benthamiana leaves. Overall these results demonstrate that cop1-6 is not a temperature-conditional allele, but this mutation allows for a partially active protein which unveils a pivotal role of active BR signaling in the control of COP1 activity.